trig
posted by Spencer on .
(cotxsec2x  cotx)/ (sinxtanx + cosx) = sinx
prove.
i keep getting (if i start from the left side) = cosx instead of sinx please help!

first of all you should have typed it correctly as
(cotxsec^2 x  cotx)/ (sinxtanx + cosx) = sinx
I read that first part as sec(2x), and wasted about 10 minutes trying to prove that.
so...
LS = [cotx(1/cos^2x  1)]/[sin^2x/cosx + cosx]
= [cotx(1  cos^2x)/cos^2x]/[(sin^x + cos^2x)cosx]
= [cotx(sin^2x/cos^2x)]/[1/cosx]
= [sinx/cosx]/[1/cosx]
= sinx
= RS